Penentuan Karyawan Terbaik pada PT Kage Dwijaya Palembang - Elviana, Shella (JATISI, 2024)
The best employees have high performance for a company, this performance is based on the values ​​and criteria that have been determined by the company. In its implementation, a decision support system (DSS) can help companies improve capabilities and make it easier for users or decision makers with several alternative options available so that the goals to be achieved can run well. PT. Kage Dwijaya, however in its implementation the employee determination is still carried out conventionally, with calculations and criteria that are not yet comprehensive so it takes 1 month. Apart from that, the assessment is also only carried out by considering the employee's communication skills. This causes other parties to feel unfair, and gives rise to various speculations. Employees often feel that the decision-making process is not transparent because the parties involved do not pay proper attention to the employee's working abilities, this can affect the performance of each employee. This research aims to design and develop the best employee selection decision support system by applying the Multi Attribute Utility Theory (MAUT) method, with the Rational Unified Process (RUP) methodology using the PHP programming language and the Laravel framework and using the MySql database. In the initial design stage, use case diagrams, class diagrams and activity diagrams are used. This research produces a decision support system that is faster and more efficient and increases employees' sense of trust in the company during the process of selecting the best employees.